The Effectiveness of Using the Classroom Guide Book for Early Childhood Education Teachers - Kartika Rinakit Adhe; Karina Dewi Masitha; Sri Widayati (Universitas Muhammadiyah Ponorogo, 2020)
This study aims to (1) to develop a classroom guide book for early childhood education (ECE) teachers that provides alternative models of class setting and seating management in the classroom, (2) to determine the feasibility of developing a classroom guide book for ECE teachers. This study used research and development method by adapting the Borg Gall. The subject in this study were ECE teachers from 7 schools in West Surabaya. Data collection techniques used were interviews, questionnaires, and observations. The research subjects in the initial research were 15 teachers, and operational research was 30 teachers. The result of this research is the development of a class setting guidebook for ECE teachers. From the product trial results, the results of the development are feasible to be used to guide teachers in choosing alternative class settings that will be used in their classrooms by 83%. Based on the initial trial scores, main trials and operational field trials (3,6) from a scale of 1-4, the class setting manual is effective for increasing teacher knowledge about the types of learning models, class settings and seating arrangements in the classroom based on interviews have been done. So it can be concluded that the guidelines for structuring children's sitting in class are effectively used and the teacher has the right reference.